The Effectiveness Method Rational - emotional, Behavioral Ellis on The Mental in The Experts Iran Khodro Diesel Company - Nila Elmy Manesh (آموزش بهداشت و ارتقاء سلامت ایران, 2017)
Background and Objective : Ellis rational emotive behavioral therapy (REBT) has been approved as a way to decrease some health problems. Therefore, it may be effective in promoting health. Therefore, this study aimed to investigate the effectiveness of REBT on the health. Methods: the research is a quasi-experimental with pre-test and post-test design. The statistical population included 650 experts working in Iran Khodro Diesel Company. 60 people were selected using random sampling method and were randomly divided into two groups. The general health questionnaire was used as a measurement tool. At first, this questionnaire was in the pre-test and the experimental group received Ellis method. Then the test was implemented in two further stages of post-test and follow-up. Data were analyzed using SPSS-16 software and variance test (ANOVA). Results: The results of the analysis showed that using Ellis health method and social functioning subscales, anxiety and depression have improved in the experimental group compared to the control group (0/88, 0/04) (P<0/01). The results of the follow-up phase indicated the sustainability and effectiveness of the intervention on health variable and subscales of social function, depression, anxiety and increasing the effect on the subscale of the physical symptoms. Conclusion: Therefore, it can be stated that Ellis method has been fruitful on the improvement of mental health and its subscales, and it is recommended that courses such as Ellis intervention program can be held in work environments.